2020
DOI: 10.1002/jat.4085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity of Ti3C2 and Nb2C Mxene quantum dots (QDs) to human umbilical vein endothelial cells

Abstract: Recently, we developed highly fluorescent Ti3C2 and Nb2C Mxene quantum dots (QDs) for labeling of in vitro models. However, the mechanism of the toxicity of the prepared QDs was not explored before. In this study, we addressed the possible mechanism associated with cytotoxicity of the QDs to human umbilical vein endothelial cells (HUVECs). Exposure to up to 100 μg/ml Ti3C2 but not Nb2C QDs for 24 h significantly induced cytotoxicity. The exposure also increased intracellular Ti and Nb elements, indicating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 38 publications
(55 reference statements)
0
30
0
Order By: Relevance
“…Meanwhile, the internalization of carbon nanotubes led to the cytotoxicity of ECs (Li et al, 2019; Suzuki et al, 2016; Valentini et al, 2018). High levels of Ti 2 C Mxene, novel 2D NMs, also induced cytotoxicity to HUVECs (Gu et al, 2021). In this study, the results suggested that GDY, novel carbon‐based 2D NMs, was as cytotoxic as GO based on the same mass concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the internalization of carbon nanotubes led to the cytotoxicity of ECs (Li et al, 2019; Suzuki et al, 2016; Valentini et al, 2018). High levels of Ti 2 C Mxene, novel 2D NMs, also induced cytotoxicity to HUVECs (Gu et al, 2021). In this study, the results suggested that GDY, novel carbon‐based 2D NMs, was as cytotoxic as GO based on the same mass concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As shown Figure 6, HUVECs were successfully labeled by Cu, N‐doped CDs with strong red fluorescence. Recently, we developed highly fluorescent MXene QDs to label in vitro models, but they also induced strong cytotoxic effects (Gu et al, 2020; Guan et al, 2019; Q. Xu et al, 2020; X. Yan, Ma, et al, 2020). Here, the data reported in this study suggested that Cu, N‐doped CDs were more biocompatible for bio‐imaging purposes (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recently developed novel MXene QDs. Although they could be used to label cells and organoids (Guan et al, 2019; Q. Xu et al, 2020; X. Yan, Ma, et al, 2020), they still induced severe cytotoxicity to endothelial cells (Gu et al, 2020). On the basis of previous observations, we are developing high‐fluorescent QDs based on other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial toxicity can therefore significantly limit the future biomedical applications of nanomaterials. [23] Furthermore, previous studies have reported that other forms of MXenes, such as Ti 3 C 2 T x MXenes, can increase cellular ROS levels, create oxidative stress to nearby cells, and cause cellular damage. [19,[39][40][41] This increase in ROS also induces the release of proinflammatory cytokines from resident tissue macrophages and interferes with anti-inflammatory and immunomodulatory properties of implanted biomaterials in the body.…”
Section: Biocompatibility Of Ta 4 C 3 T X Mqdsmentioning
confidence: 99%